Targeting viral Fe-S clusters with TEMPOL confers broad-spectrum anti-coronavirus activity - Leyu Hu; Lexi Gao; Xingwei Fu; Zesheng Rong; Yue Cheng; Yuhan Hou; Lu Han; Xin Ran; Guiwen Guan; Ting Zhou; Lingling Chang; Xiaomin Zhao; et al. (Veterinary Microbiology, 2026)

NIR-elicited hydrogel contraction modulates rheological dynamics for spatiotemporally controlled metallo-drug release to potentiate cuproptosis-driven immunotherapy - Wenpei Luo; Lingyun He; Weiwei Liu; Xin Gao; Long Cheng; Min Zheng; Jianli Ren; Haitao Ran; Xun Guo; Lu Yang (Chemical Engineering Journal, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Single-cell sequencing reveals metabolic reprogramming and immune regulation underlie the maintenance of teleost granulomas - Zheng-Yang Zhou; Zheng-Ran Jian; Jin-Lai Gu; Xin-Yuan Jiang; Jie He; Yuan-Chang Gao; Sheng Lian; Shang-Jie Bai; Chen-Wang Lu; Lin-Feng Kuang; Ming-Zhu Liu; Peng-Fei Li; et al. (Fish & Shellfish Immunology, 2026)

Deciphering the regulatory role of the pfs gene on biofilm formation in Lactobacillus plantarum R: Insights from transcriptome and metabolome - Xin Fan; Bo Li; Xinao Xu; Binbin Long; Zhiwen Jia; Ran Wang; Junjun Gao; Yang Chen; Mingye Peng; Mengzhou Zhou (Bioresource Technology, 2026)

Breaking the antimicrobial resistance dilemma: marine natural products, a treasure trove for the development of new anti-Staphylococcus aureus drugs - Peng-Jie Li; Liu-Xia Lv; Xi-Zhen Cao; Jian-Yu Liu; Ji-Xiu Gao; Hao-Ran Li; Gulab Said; Dan Chen; Bo Yao; Xin Liu; Mei-Yan Wei; Xiao-Ping Yang; et al. (Marine Life Science & Technology, 2026)
Antimicrobial resistance (AMR) affects multiple fields, including medicine, pharmacy, food safety, and animal husbandry, and poses a major threat to public health and economic development. Staphylococcus aureus has emerged as one of the most critical bacterial pathogens due to its widespread prevalence and significant genetic plasticity. This review outlines currently approved small-molecule drugs for clinical use and their mechanisms in controlling bacterial infections and antimicrobial resistance, highlighting the development of novel agents as an effective strategy to combat AMR. Special emphasis is placed on the antibacterial activity of marine-derived natural products (MNPs) against S. aureus , and a systematic analysis is presented for the first time on the structures, origins, activities, and structure–activity relationships of 1,192 compounds reported in 468 publications from 1977 to 2025. Among these, 36 MNPs exhibited significant activity against both methicillin-sensitive S. aureus and methicillin-resistant S. aureus (MIC ≤ 1 µg/mL). Macrolides and peptides represented the most prevalent structural classes, with compounds displaying potent activity accounting for 24% and 27% of the total active compounds, respectively. Further drug-likeness analysis shows that MNPs have promising therapeutic potential. Among the 160 highly active MNPs, over 80% have suitable lipid-water partition coefficients, and 41% fully meet Lipinski's Rule of Five. Structural analysis reveals tetrahydrofuran, tetrahydropyran, and sugar units as the most common motifs, present in 20, 16, and 14 compounds, respectively. Technologies and strategies to accelerate the development of marine-derived antibacterial drugs are also proposed. This will serve stakeholders across diverse sectors by supporting cross-sectoral coordination to address AMR.

Unveiling the molecular mechanisms of dihydromyricetin regulating the biosynthesis of three key secondary metabolites in Monascus purpureus HBSD08 through integrated transcriptomic and metabolomic analyses - Ran Fang; Yingying Wang; Jie Qiao; Di Wu; Qianyu Gao; Chunzheng Han; Penghui Sun; Wanting Wang; Xin Zeng; Bingyue Xin; Biao Zhang; Deyin Zhao; et al. (Food Bioscience, 2026)

Bacterial, viral and environmental interactions shape antibiotic resistance genes in China's anaerobic-anoxic-oxic wastewater treatment systems - Qian Liu; Jie Chen; Ran Xu; Cong Huang; Nanqi Ren; Shuhong Gao; Wei Li; Xiaodong Xin; Sihao Lv; Siqi Yang; Weiwei Ben; Ai-Jie Wang (Water Research, 2026)

Role of Ni-Co bimetals in CaCr2O4 catalysts for dry reforming of methane: Promotion in coke resistance - Jie Gao; Hangjia Zhang; Jingyu Ran; Chuan Ma; Xin Huang; Yunlin Shao; Huayu Qiu; Zhiliang Ou; Lei Tang (Fuel, 2026)

Close-packed metal organic frameworks enabled high-energy solid-state lithium metal batteries - Yining Zhang; Hongsheng Shi; Yuyao Zhang; Xin Chen; Shuanghong Wang; Jinjiang Liang; Qiong Yuan; Tianyi Gao; Ran Wei; Haochen Zhang; Tao Li; Tianquan Lin; et al. (Chemical Engineering Journal, 2026)

Evaluation of Lentilactobacillus kefiri NM119–2 as a novel probiotic in fermented milk: functional properties and metabolic impact - Baoyi Yuan; Xiangyun Liu; Jianan Li; Ran Gao; Xin Zhao; Lai-Yu Kwok; Qiuhua Bao (Food Research International, 2025)

A copper-based single-atom material effectively controls plant diseases with nearly zero soil residue and low phytotoxicity - Rui Huang; Yong Yan; Yafei Jiang; Chunyan Gu; Zhentao Ma; Lifang Xue; Yao Ma; Xingen Lin; Juan Zhang; Ran Shi; Yiwen Wang; Linjing Liu; et al. (Science Bulletin, 2025)

Unraveling the surface and interface reaction mechanisms of CO2 hydrogenation to methanol over Ga-modified Cu-based catalysts: Insights from DFT calculations - Jie Gao; Hangjia Zhang; Jingyu Ran; Guohua Sang; Zhiliang Ou; Lei Tang; Huayu Qiu; Yunlin Shao; Chuan Ma; Xin Huang (Journal of Environmental Chemical Engineering, 2025)

Highly selective and sensitive detection of β-lactam antibiotics in food samples using a fluorescent turn-on probe based on metal-organic framework - Ran An; Rui-Xuan Li; Xin Shang; Chang-Qi Fu; En-Qing Gao; Qi Yue (Food Chemistry, 2025)

A two-level turbulent density-based topology optimization method: A low-resistance U-bend channel flow - Yan Tian; Ran Gao; Yi Wang; Angui Li; Xin Dong; Tong Li; Shengrui Yu (Building and Environment, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Enhanced La0.875Ce0.125CoO3 catalyst for Hg0 removal from low-temperature flue gas: H2O and SO2 resistance performance and mechanism - Jie Gao; Zijun Ran; Jingyu Ran; Xin Huang; Chuan Ma; Yunlin Shao (Fuel, 2025)

Osmotic and cold stress-induced viable but non-culturable state in Lacticaseibacillus paracasei Zhang: A transcriptome analysis - Qiuhua Bao; Baoyi Yuan; Xuebo Ma; Xin Zhao; Ran Gao; Jianan Li; Lai-Yu Kwok (International Dairy Journal, 2025)

A green-solvent processed multifunctional bamboo composite with high strength, robust fire retardancy, and dimensional stability - Xiangyu Ren; Huijun Zhang; Weibing Xue; Tongda Liu; Rong Liu; Xin Ran; Ping Wang; Wei Gao; Yanmei Li; Guanben Du; Long Yang (Chemical Engineering Journal, 2025)

Topology optimization of bend for reducing the local resistance in a piping and duct system - Yan Tian; Ran Gao; Ruoyin Jing; Yi Wang; Angui Li; Xin Dong; Xinpeng Hao; Zheng Ji (Building and Environment, 2025)

Sleep deprivation stimulates adaptive thermogenesis by activating AMPK pathway in mice - Tian-Shu Zheng; Xin-Ran Gao; Rui-Ping Xu; Yi-Fei Zhao; Zhi-Teng Yang; De-Hua Wang (Journal of Comparative Physiology B, 2025)

Enhanced priming effect in agricultural soils driven by high-quality exogenous organic carbon additions: A meta-analysis - Yuyao Zhang; Hongyu Hu; Yiguo Ran; Ping Huang; Yunlong Cai; Lin Chen; Congzhi Zhang; Xin Gao; Donghao Ma; Jiabao Zhang (Science of The Total Environment, 2025)

Biodegradation of imidacloprid and diuron by Simplicillium sp. QHSH-33 - Ke Xu; Xin-Ran Ke; Wan-Ting Zhang; Xin-Yuan Wu; Zhi-Jun Song; Mei-Juan Jiao; Xiao-Juan Gao; Li Zhou; Hong-Yan Ji; Fang Wang; Xiu-Li Wu (Pesticide Biochemistry and Physiology, 2024)

The role of Nocardia seriolae-induced autophagy in the development of chronic inflammation in the liver and the formation of granulomas in largemouth bass (Micropterus salmoides) - Shang-Jie Bai; Zheng-Ran Jian; Sheng-Yu He; Lin-Feng Kuang; Zheng-Yang Zhou; Chen-Wang Lu; Zhen-Dong Zhong; Jie He; Quan-Xin Xiong; Shuang-Yan Xiao; Peng-Fei Li; Ming-Zhu Liu; et al. (Aquaculture, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Pathogenesis-Related Protein 10 Family Genes Involved in Sugarcane Responses to Biotic Stressors and Salicylic Acid - Liang-Nian Xu; Xia-Ran Jiang; Jia-Xin Lin; Juan Li; Talha Javed; Jian-Ying Zhao; San-Ji Gao (Journal of Plant Growth Regulation, 2024)

Experimental evidence that nitrogen-fixing cyanobacterium Trichodesmium spp. supplies new nitrogen source to marine phytoplankton - Shuang-Qing Li; Yan Xiao; Hai-Long Huang; Zhen Luo; Tao-Ran Sun; Hua-Yang Gao; Xin-Wei Wang; Hai-Bo Jiang (Frontiers in Marine Science, 2024)
In oligotrophic oceans, primary productivity is widely limited by nitrogen bioavailability. The broadly distributed and abundant nitrogen-fixing cyanobacterium Trichodesmium plays an important role in the oceanic nitrogen and carbon cycles by providing a “new” source of nitrogen to many non-diazotrophic microbes, thereby driving new primary production in the ocean. However, the underlying process and mechanism of nitrogen supply from Trichodesmium to other phytoplankton remain unclear. Here, our results demonstrated that the fixed nitrogen released by Trichodesmium could sustain the growth of a non-nitrogen-fixing cyanobacterium Synechococcus sp. PCC 7002, including a mutant strain (Mut- ureA ) that cannot use urea. However, the growth rate of Mut- ureA was approximately 20% lower than that of the wild strain when Trichodesmium filtrate was used for nitrogen supply. This result was consistent with the composition of the Trichodesmium exudate, in which urea comprised more than 20% of the total fixed nitrogen that was released. It is evident from the experiments that a fraction of the Trichodesmium -derived nitrogen was not available to Mut- ureA . Our results suggested that Trichodesmium produces dissolved organic nitrogen, especially a certain amount of urea as a “new” nitrogen source, benefiting in particular populations of surrounding phytoplankton species.

Mitochondrial damage and activation of NLRP3 induced by Yersinia ruckeri infection play an important role in the occurrence of diffuse acute inflammation of channel catfish (Ictalurus punctatus) - Chen-Wang Lu; Jie He; Quan-Xin Xiong; Zhen-Dong Zhong; Bin Yang; Sheng Lian; Meng-Meng Wang; Shang-Jie Bai; Lin-Feng Kuang; Zheng-Yang Zhou; Zheng-Ran Jian; Yuan-Chang Gao; et al. (Aquaculture, 2024)

The fabrication of Mn single atoms/clusters on Al2O3 for enhanced catalytic NO oxidation - Xiao-Ke Hou; Hui-Xin Zhang; Yi-Bo Wang; Jin-Ping Zhang; Xin Gao; Lei Chen; Chao Li; Hong-Mei Jing; Chi He; Qiang Lu; Chun-Ran Chang (Fuel, 2024)

Reactive oxygen species (ROS) modulate nitrogen signaling using temporal transcriptome analysis in foxtail millet - Hui-Xin Meng; Yu-Ze Wang; Xin-Li Yao; Xin-Ran Xie; Shuqi Dong; Xiangyang Yuan; Xiaorui Li; Lulu Gao; Guanghui Yang; Xiaoqian Chu; Jia-Gang Wang (Plant Molecular Biology, 2024)

Zonation of bulk and rhizosphere soil bacterial communities and their covariation patterns along the elevation gradient in riparian zones of three Gorges reservoir, China - Weitao Jia; Ping Huang; Kai Zhu; Xin Gao; Qiao Chen; Jilong Chen; Yiguo Ran; Shanshan Chen; Maohua Ma; Shengjun Wu (Environmental Research, 2024)

Increasing lateral transport of soil and carbon on the Tibetan Plateau - Yanzhang Huang; Zhongbao Xin; Guangyao Gao; Xixi Lu; Lishan Ran; Yafeng Wang; Zhiqiang Zhang (CATENA, 2024)

Dopant-Enhanced harmonization of α-Fe2O3 oxygen migration and surface catalytic reactions during chemical looping reforming of methane - Hui-Xin Zhang; Xi-Yang Yu; Xue Su; Xin Gao; Zheng-Qing Huang; Bolun Yang; Chun-Ran Chang (Chemical Engineering Journal, 2024)

Ionic liquids bonded in mesoporous HAP serve as efficient catalysts for CO2 fixation - Decun Luo; Zhen-Yu Zhang; Hao Yuan; Xi-Yang Yu; Xin Gao; Zhun Hu; Chun-Ran Chang (Chemical Engineering Journal, 2024)

Na2S-modified biochar for Hg(II) removal from wastewater: A techno-economic assessment - Wenwen Zhao; Zhongsheng Zhang; Yuan Xin; Ran Xiao; Feng Gao; Haitao Wu; Wenfeng Wang; Qiang Guan; Kangle Lu (Fuel, 2024)

Climate-shaped vegetation dominated the spatial pattern of the Bowen ratio over terrestrial ecosystems in China - Mingyu Sun; Guirui Yu; Zhi Chen; Tianxiang Hao; Meng Yang; Xianjin Zhu; Weikang Zhang; Lang Han; Zhaogang Liu; Lexin Ma; Xiaojun Dou; Yuan Yao; et al. (Agricultural and Forest Meteorology, 2024)

Low-resistance local components design method based on topology optimization: A case study of a duct tee - Yan Tian; Ran Gao; Mengchao Liu; Angui Li; Xin Dong; Shengrui Yu; Xiaojie Xie; Tong Li; Pengfei Si (Building and Environment, 2023)

Design of a novel chimeric peptide via dual blockade of CD47/SIRPα and PD-1/PD-L1 for cancer immunotherapy - Zheng Hu; Wanqiong Li; Shaomeng Chen; Danhong Chen; Ran Xu; Danlu Zheng; Xin Yang; Shuzhen Li; Xiuman Zhou; Xiaoshuang Niu; Youmei Xiao; Zhuoying He; et al. (Science China Life Sciences, 2023)

The effect of chlorogenic acid, a potential botanical insecticide, on gene transcription and protein expression of carboxylesterases in the armyworm (Mythimna separata) - Dong-jiang Lin; Ya-xin Zhang; Yong Fang; San-ji Gao; Ran Wang; Jin-da Wang (Pesticide Biochemistry and Physiology, 2023)

Cross-linked entanglement of aldehyde and amine-functionalized nanocellulose reinforced with biomineralization to produce an all-bio-based adhesive - Kelu Ni; Guanben Du; Chuanyin Liu; Yingchen Wu; Hongxing Yang; Chunyan Yin; Hang Su; Xin Ran; Wei Gao; Long Yang (Chemical Engineering Journal, 2023)

Efficient catalytic oxidation of chlorinated volatile organic compounds over RuO2-WOx/Sn0.2Ti0.8O2 catalysts: Insight into the Cl poisoning mechanism of acid sites - Feiyi Zhou; Qi Xin; Yujie Fu; Zhesheng Hua; Yi Dong; Mingchu Ran; Hao Song; Shaojun Liu; Ruiyang Qu; Yang Yang; Xiao Zhang; Chenghang Zheng; et al. (Chemical Engineering Journal, 2023)

Activated wood surface and functionalized cellulose co-building strong chemical wood bonding performance - Tongda Liu; Guanben Du; Yingchen Wu; Chang Liu; Hongxing Yang; Kelu Ni; Chunyan Yin; Xin Ran; Wei Gao; Long Yang (Carbohydrate Polymers, 2023)

Visualization experiment and flow homogenization optimization of the multi-path plenum chamber system using a perforated plate - Wanqing Zhang; Angui Li; Ran Gao; Xin Gao; Changqing Yang (Building and Environment, 2023)

High-strength, self-initiated, wide pH range of underwater adhesive suitable for different severe environments - Junyu Ren; Guanben Du; Sichen Liu; Hongxing Yang; Xin Ran; Chang Liu; Tongda Liu; Zhi Li; Xiaojian Zhou; Wei Gao; Bei Zhou; Long Yang (Chemical Engineering Journal, 2023)

Discovery of potent and selective acetylcholinesterase (AChE) inhibitors: acacetin 7- O -methyl ether Mannich base derivatives synthesised from easy access natural product naringin - Hao-ran Liu; Xue Men; Xiao-hui Gao; Lin-bo Liu; Hao-qun Fan; Xin-hua Xia; Qiu-an Wang (Natural Product Research, 2018)

Isolation and molecular characterization of two novel HMW-GS genes from Chinese wheat (Triticum aestivum L.) landrace Banjiemang - Hui Shao; Tian-hong Liu; Cong-Fu Ran; Li-Qun Li; Jing Yu; Xin Gao; Xue-Jun Li (Genes & Genomics, 2015)